2016
DOI: 10.3109/08820538.2015.1119858
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary RNFL Thickness Changes Evaluated with Spectral Domain Optical Coherence Tomography after Uncomplicated Macular Surgery for Epiretinal Membrane

Abstract: The selective decrease in the temporal and inferior p-RNFL thickness after vitrectomy for ERM removal could indicate inner retinal damage related to ILM peeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…In the past, a large number of studies [18][19][20][21] have focused on the changes in microstructure of fovea due to iERM in order to identify the anatomic changes associated with the vision recovery after surgery. This included the integrity of ellipsoid zone, the central macular thickness (CMT) and the photoreceptor outer segments.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, a large number of studies [18][19][20][21] have focused on the changes in microstructure of fovea due to iERM in order to identify the anatomic changes associated with the vision recovery after surgery. This included the integrity of ellipsoid zone, the central macular thickness (CMT) and the photoreceptor outer segments.…”
Section: Discussionmentioning
confidence: 99%
“…After analyzing our results, we have found that there is a statistically significant increase in the RNFL thickness in the first month after temporal quadrant surgery ( Figure 2 ). It is probably associated with edema of the nerve fibers because of the axonal transport disorder leading to apoptosis and atrophy of the ganglion cells [ 7 , 16 , 17 ], which leads to the subsequent RNFL thinning 6 months after the procedure. Another explanation of this mechanism may be dehydration caused by the fluid to air exchange during PPV, toxic retinal damage with gas endotamponade, and mechanical damage during the removal of the vitreous body [ 7 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is probably associated with edema of the nerve fibers because of the axonal transport disorder leading to apoptosis and atrophy of the ganglion cells [ 7 , 16 , 17 ], which leads to the subsequent RNFL thinning 6 months after the procedure. Another explanation of this mechanism may be dehydration caused by the fluid to air exchange during PPV, toxic retinal damage with gas endotamponade, and mechanical damage during the removal of the vitreous body [ 7 , 16 , 17 ]. Like Gharbiya et al [ 16 ], we did not notice any differences in the RNFL thickness between patients who underwent phacovitrectomy and those who underwent vitrectomy alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Статистически достоверное истончение слоя нерв-ных волокон сетчатки в обеих группах затронуло лишь темпоральный сектор (RNFL-T), что полностью соответ-ствует описанному в литературе представлению о наи-большей восприимчивости данного сектора [14,18,19].…”
Section: Discussionunclassified